2022
DOI: 10.2298/tsci200414056b
|View full text |Cite
|
Sign up to set email alerts
|

The CFD studies on the influence of un-wetted area on the heat transfer performance of the horizontal tube falling film evaporation

Abstract: This paper discusses about the effect of un-wetted area of tube on the heat transfer performance of horizontal tube falling film evaporation. A 2D CFD model was developed to perform simulations and investigate the output and validated them with published data available in the literature. In the present study the VOF method is used to track the boundary of the liquid vapour from the contours of volume fraction. Effect of varying tube wall temperature or wall super heat (6 to 11?C) on un-wetted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It was found that a thicker wavy film was formed over the tube as a result of the upward air streams. Balaji et al confirmed that the heat transfer coefficient declined at the local dryout in a horizontal tube evaporator. Additionally, the mass transfer coefficient increased with wall superheat increased from 6 to 9 K, and then keep almost unchanged with the increase of superheat.…”
Section: Phase Change For Separation and Purificationmentioning
confidence: 93%
See 3 more Smart Citations
“…It was found that a thicker wavy film was formed over the tube as a result of the upward air streams. Balaji et al confirmed that the heat transfer coefficient declined at the local dryout in a horizontal tube evaporator. Additionally, the mass transfer coefficient increased with wall superheat increased from 6 to 9 K, and then keep almost unchanged with the increase of superheat.…”
Section: Phase Change For Separation and Purificationmentioning
confidence: 93%
“…The Tanasawa model is a simplified version of the Schrage model, which assumes that the mass flux is linearly related to the temperature jump when the difference between the interface temperature and saturation temperature is tiny . However, the determination of key empirical coefficients ( r or w ) in Hertz–Knudsen relations can be challenging as they are not constant in different phase change processes and are varying with the configuration, surface roughness, local superheat, saturation temperature, and dryout. , There are still other well-known phase change models, such as Rohsenow, Hardt and Wondra, De Schepper et al, Ganapathy et al, and the energy jump model . These correlations are commonly used in the gas–liquid phase change with a large-scale interface.…”
Section: Cfd Approaches For Phase Change Simulationmentioning
confidence: 99%
See 2 more Smart Citations